Hubungan Beban Kerja, Kelelahan Mental, dan Kesadaran K3 pada Nelayan - Irma Fajriah; Muhammad Ikhsan Rauf (VitaMedica : Jurnal Rumpun Kesehatan Umum, 2026)
The fisheries sector is an important economic element but has high safety risks for fishermen due to harsh working conditions. This study aims to analyze the relationship between workload, mental fatigue, and Occupational Safety and Health (OHS) awareness among fishermen. This study uses a cross-sectional design with a quantitative descriptive-analytical approach4. Data were collected through questionnaires from active fishermen selected using a purposive sampling technique, with measurement instruments including NASA-TLX for workload and MFI-20 for mental fatigue. The results of the descriptive analysis show that most respondents are in the high workload (45%) and high mental fatigue (45%) categories, while the level of OHS awareness tends to be low (40%). Spearman's correlation test showed a significant positive relationship between workload and mental fatigue ($r = 0.612; p < 0.05), as well as a significant negative relationship between mental fatigue and OSH awareness ($r = -0.497; p < 0.05). This study concluded that workload indirectly influences OSH awareness through mental fatigue as an intermediary variable.8 These findings emphasize the importance of workload management and psychological interventions to improve fishermen's safety behavior at sea.